2017
DOI: 10.1021/acsami.7b07100
|View full text |Cite
|
Sign up to set email alerts
|

Construction of MoO2 Quantum Dot–Graphene and MoS2 Nanoparticle–Graphene Nanoarchitectures toward Ultrahigh Lithium Storage Capability

Abstract: Herein, MoO quantum dots (QDs; <5 nm) are synthesized through a one-step solvothermal process. MoO QD-bonded graphene sheets (MoO-QDs@RGO) are facilely produced and can be further converted through sulfidation into MoS nanoparticle-bonded graphene sheets (MoS-NPs@RGO). The novel MoO-QDs@RGO electrodes demonstrate exceptionally attractive lithium storage capability (e.g., 1257 mA h g at 100 mA g, being close to the highest values ever reported for a MoO-based lithium ion battery electrode), rate capability, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 73 publications
1
28
0
Order By: Relevance
“…Yu et al 94 produced ZnS QDs-GR nanocomposites via a facile solvothermal method, their work would be a value to design the procedure of metal sul¯de decorated GR with further excellent properties. In 2017, Wang et al 95 synthesized MoO 2 QDs/GR through a novel facile and scalable solvothermal method. The MoO 2 QDs/GR electrodes exhibit remarkably superior lithium storage capability, outstanding cycling stability and rate retention.…”
Section: Solvothermal Methodsmentioning
confidence: 99%
“…Yu et al 94 produced ZnS QDs-GR nanocomposites via a facile solvothermal method, their work would be a value to design the procedure of metal sul¯de decorated GR with further excellent properties. In 2017, Wang et al 95 synthesized MoO 2 QDs/GR through a novel facile and scalable solvothermal method. The MoO 2 QDs/GR electrodes exhibit remarkably superior lithium storage capability, outstanding cycling stability and rate retention.…”
Section: Solvothermal Methodsmentioning
confidence: 99%
“…Studies have shown that smaller-sized nanoparticles in the metal oxide/rGO composites have shorter ion/electron transport channels, lesser stress changes during electrochemical cycling, and a larger reaction active area, which are beneficial to improve the rate capability and cycling stability. ,,,, Quantum dots (QDs) with a diameter of 2–20 nm have unique physical and chemical properties . Wang et al . reported that MoO 2 QDs@RGO demonstrated a lithium storage capability of 1257 mA h g –1 at 0.1 A g –1 .…”
Section: Introductionmentioning
confidence: 99%
“…9,11,16,19,25 Quantum dots (QDs) with a diameter of 2−20 nm have unique physical and chemical properties. 12 Wang et al 26 reported that MoO 2 QDs@RGO demonstrated a lithium storage capability of 1257 mA h g −1 at 0.1 A g −1 . Yang et al 27 synthesized that carbon-coated ZnO QDs exhibited a specific charge capacity of 1200 mA h g −1 at 0.075 A g −1 and a rate capability of 400 mA h g −1 at 3.75 A g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…34,39 Second, the nanosized CoO grains enable complete lithiation/delithiation is kinetically possible with curtate lithium-ion diffusion paths in grain interior and between neighbouring grains. 36,40 This in turn prevents generation of inactive lithium. Third, the resulting nanoscaled cobalt metal grains accompanied by the lower transformation active energy can promote the reversibility of the conversion reaction.…”
Section: Introductionmentioning
confidence: 99%
“…These gaps not only provide fast lithium-ion transfer channels but also retard the electrolyte permeation inside the CNB. The confined electrode–electrolyte contact area is in favor of limiting most SEI formation to the outer surface instead of individual nanograins. , Second, the nanosized CoO grains enable complete lithiation/delithiation is kinetically possible with curtate lithium-ion diffusion paths in grain interior and between neighbouring grains. , This in turn prevents generation of inactive lithium. Third, the resulting nanoscaled cobalt metal grains accompanied by the lower transformation active energy can promote the reversibility of the conversion reaction. , As a consequence of the mechanism, the CoO-CNB electrode can upgrade ICE to a high value of 82.2%, which is among the highest values in TMO anodes reported.…”
Section: Introductionmentioning
confidence: 99%